Sound behaviour of humpback whales (Megaptera novaeangliae) on summer feeding grounds in Northeast Icelandic waters - Arnar Björnsson 1987- (2014)
The humpback whale (Megaptera novaeangliae) is a migratory species, which possesses a complex sound repertoire. This ranges from simple non-song sounds, referred to as social sounds, to complex mating songs. Non-song sounds have been reported on their feeding and breeding grounds. There is a considerable lack of understanding about the role of these non-song sounds due to relatively few publications, especially from high latitude feeding grounds. The aim of this research was to gain better understanding on the role of these social sounds on a high latitude feeding ground. The sound behaviour was studied in relation to their visually observed behaviour, on summer feeding grounds in Skjálfandi Bay, NE-Iceland. Passive acoustic recordings with hydrophones and video recordings of surface behaviour were conducted simultaneously. The study periods were July–August 2012, and June–July 2013. Each detected vocalisation was inspected visually and aurally with a spectrogram. Statistical analysis was then used to determine correct classification of vocalisation types. All that combined had the purpose of getting synchronized behaviour and acoustic results, for sound associated behaviour. During this research, a total of 161 humpback whale vocals were recorded. These vocals were categorized into 11 vocal types. The most frequently detected type was a harmonic “upsweep grunt”. Feeding behaviour was the most frequently observed behaviour state, for a total of 27 sighted individual humpback whales, in both study periods. Group behaviour was rarely encountered in the research and never more than pairs. Most vocals were detected while feeding behaviour was observed. Hnúfubakurinn (Megaptera novaeangliae) er fardýr sem gefur frá sér flókið samsafn hljóða. Þessi hljóð geta verið einföld félagshljóð eða flóknari söngvar, sem gjarnan hafa verið tengdir við mökunartímabil hnúfubaka. Félagshljóð hafa verið greind bæði á fæðustöðvum og mökunarstöðvum. Fáar rannsóknir hafa farið fram á þessari gerð hljóðmyndunar, einkum á fæðustöðvum á ...